Comportamento mecânico de instrumentos endodônticos de NiTi: uma abordagem numérica - Suzanny Cristina Soares Martins (2020)
Nickel-titanium (NiTi) rotary instruments are better than stainless steel instruments due to the superelasticity and the shape memory properties. Also, NiTi has superior mechanical behavior, biocompatibility, corrosion resistance, and high ductility. The great flexibility of endodontic files allows the correct shaping of root canals. Flexibility in NiTi files is related to superelasticity, which depends on crystallographic phases present and geometry of these instruments. NiTi files must be flexible to prevent damage to the dental canal, but they also need high mechanical strength to promote cutting efficiency. Such properties can be enhanced by changes in design, heat treatments, and the manufacturing process. Within this context, the objective of this work is to evaluate, by the finite element method, the changes in the mechanical behavior of rotary endodontic instruments as a result of different heat treatments and geometric variations. For this, it was verified the effects that off-centered cross-section causes in NiTi files and two geometrically different instruments were compared applying three heat treatment conditions. Bending and torsion loads were performed on the files, using finite elements, and flexibility, torsional stiffness, and stress distribution were checked. The results showed that the geometric eccentricity does not increase the flexibility of the instruments, but alters the stress pattern, decreasing the maximum stress reached. There is an increase in fatigue life due to the lower stress, and the eccentric geometry makes it possible to format larger canals using a smaller cross-section area. The comparison between the two designs showed that the cross-sectional area directly affects the flexibility and torsional stiffness. The stress distribution is related to other geometric factors, such as pitch numbers, shape, and eccentricity of the cross-section. About heat treatments, it was found that obtaining the R phase promotes a higher level of flexibility and a lower level of stress to files than the superelastic NiTi.